Antibiotic duration and timing of the switch from intravenous to oral route for bacterial infections in children: systematic review and guidelines. Issue 8 (August 2016) - McMullan, Brendan J; Andresen, David; Blyth, Christopher C; Avent, Minyon L; Bowen, Asha C; Britton, Philip N; Clark, Julia E; Cooper, Celia M; Curtis, Nigel; Goeman, Emma; Hazelton, Briony; Haeusler, Gabrielle M; et al.
Summary: Few studies are available to inform duration of intravenous antibiotics for children and when it is safe and appropriate to switch to oral antibiotics. We have systematically reviewed antibiotic duration and timing of intravenous to oral switch for 36 paediatric infectious diseases and developed evidence-graded recommendations on the basis of the review, guidelines, and expert consensus. We searched databases and obtained information from references identified and relevant guidelines. All eligible studies were assessed for quality. 4090 articles were identified and 170 studies were included. Evidence relating antibiotic duration to outcomes in children for some infections was supported by meta-analyses or randomised controlled trials; in other infections data were from retrospective series only. Criteria for intravenous to oral switch commonly included defervescence and clinical improvement with or without improvement in laboratory markers. Evidence suggests that intravenous to oral switch can occur earlier than previously recommended for some infections. We have synthesised recommendations for antibiotic duration and intravenous to oral switch to support clinical decision making and prospective research.